The First Amendment to the United States Constitution and the implied freedom of political communication in the Australian Constitution. (September 2019) - Gray, Anthony Davidson
This article suggests that the Australian High Court might usefully utilize more of the First Amendment jurisprudence than it has done so to date. After a succinct summary of the Australian implied freedom and First Amendment case law, it documents cases in which the Australian High Court has either utilised, or not utilised, First Amendment case law. It suggests specific instances in which the Australian case law might utilize some of the American doctrine, and responds to suggestions that the American case law is not applicable to the Australian constitutional context.